Levando a piada a sério : o texto humorístico do entretenimento político - Marchioro, Marcell Machado (2021)
Humor is part of the human nature. The quest, throughout history, to understand its origins and effects demonstrated humor’s ability to promote momentary relief or channel energy into practice (MORREALL, 2009; SALIBA, 2018). It doesn’t come as a surprise that comedy has been applied as strategy with political effect for a long time (BAKHTIN, 1993). On media, programming that explores and discussess political affairs through a comedic outlook are recurrent and make up the discursive mode named by Young and Gray (2015) as “political entertainment”. In this study, the format’s humorous text received attention. We set to identify and comprehend the political entertainment jokes’ characteristics and its manifestation in the current media environment, both in Brazil and the U.S, through three examples: Full Frontal with Samantha Bee, The Late Show with Stephen Colbert e Greg News com Gregório Duvivier. The results show a consistency between the political entertainment’s humorous text and the joke format, and unviel its laugh-provoking mechanisms, targets and its relation to the political context of said period. Ultimately, it was possible to expand the understanding about political entertainment and humor in its use as a communication strategy.